Identification of Land Use Coverage through Ground Check GPS Data (Case Study in Tapaktuan District) - Safridatul Audah; Mislina Mislina; Afdal Afdal; Muharratul Mina Rizky (Jurnal Inotera, 2020)
Tapaktuan is a region of the west coast of Aceh which has high forest and biodiversity potential in Indonesia because most of this region is part of the Leuser Ecosystem which is known to have high biodiversity and needs to be preserved. land conversion is a big challenge for this region because of development and development activities as well as population growth. The purpose of this study is to identify land use using GPS devices. The method is by first grounding the field with GPS MAPS GARMIN type 60 CSx then the data is stored on the device. Next determine the position of the object points and then input using Mapsource software to be processed into ArcGIS. to obtain information in the field in the form of observations of land cover in the field and the coordinates. Based on the results of groundchek observations in the field as many as 299 points obtained 7 types of land cover in the field consisting of bodies of water, forests, plantations, dryland agriculture, vacant land, settlements, and shrubs. The coordinates were taken covering 15 villages in the Tapaktuan sub-district, South Aceh Regency.